An examination of skill requirements for augmented reality and virtual reality job advertisements. Issue 1 (February 2023) - Verma, Amit; Purohit, Pratibha; Thornton, Timothy; Lamsal, Kamal
The fields of augmented reality (AR) and virtual reality (VR) have seen massive growth in recent years. Numerous degree programs have started to redesign their curricula to meet the high market demand for people qualified to fill related job positions. In this paper, the authors perform a content analysis of online job postings hosted onIndeed.com and provide a skill classification framework for AR/VR job positions. Furthermore, they present a ranking of the relevant skills for such positions. The paper contributes to the extant literature on curriculum design in degree programs by presenting the popular skills in the AR/VR domain.